2023
DOI: 10.1002/tox.23735
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate metabolism in Tetrahymena thermophila: A shotgun proteomic analysis approach

Abstract: Glyphosate is one of the most widely used herbicides in the world. However, because of its overuse and resistance to degradation, high levels of glyphosate residues in the environment are reported. Therefore, this study aimed to investigate the effects of glyphosate on proteomic aspects of Tetrahymena thermophila and their uses as bioindicators of freshwater ecosystem. First, an acute toxicity test was performed to determine the median inhibition concentration (IC 50 ). The toxicity test results showed that gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that omics technology is an excellent method for revealing the metabolism and toxic mechanism of environmental toxins. Manan et al found that T. thermophila was equipped with glyphosate detoxification and degradation mechanisms based on the proteomics approach 22 . Qi et al found that GBH disrupts energy metabolism and activates an inflammatory response in mice liver through RNA‐seq analysis 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that omics technology is an excellent method for revealing the metabolism and toxic mechanism of environmental toxins. Manan et al found that T. thermophila was equipped with glyphosate detoxification and degradation mechanisms based on the proteomics approach 22 . Qi et al found that GBH disrupts energy metabolism and activates an inflammatory response in mice liver through RNA‐seq analysis 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Manan et al found that T. thermophila was equipped with glyphosate detoxification and degradation mechanisms based on the proteomics approach. 22 Qi et al found that GBH disrupts energy metabolism and activates an inflammatory response in mice liver through RNA-seq analysis. 23 Moreover, numerous studies have highlighted the power of multi-omics analysis technologies to elucidate the pathogenesis and mechanisms of lesions caused by environmental pollutants.…”
mentioning
confidence: 99%